Obtaining parameters of granulometric characteristics of suspension with usage computer controlled sedimentation balance - Kowalski, W.; Banas, M. (Видавництво Національного університету «Львівська політехніка», 2004)
Розглянуто метод отримання характеристик гранульованої суспензії шляхом використання комп’ютерного контролю над балансом під час формування осаду. Описано аналітичний шлях інтерпретації зчитаних даних використанням чисельних процедур мінімізації. Подано авторську програму, яка контролює вимірювання. Автор наводить екземпляри результатів вимірювань та моделювання, які підтверджують відповідність результуючих гранулометричних характеристик з дослідженнями, проведеними в лабораторному резервуарі. In this paper the method of the obtaining of the suspension granulometric characteristic with usage computer controlled sedimentation balance was shown. The analytical way of readings interpretation by use the numerical procedures of minimize was described. The author’s software controlled the measure was described. The authors enclosed the exemplary measures results and simulations, confirmed the conformity of the granulometric characteristics results with the sedimentation investigations in a reference laboratory settling tank.